THE ART OF ACTING: ISSUES OF TRADITION AND PROGRESS - Bekniyazova Gulbaxar; Karamatdinova Ulmanay (Лучшие интеллектуальные исследования, 2023)
Annotation: This article delves into the dynamic interplay between tradition and progress in the realm of acting, exploring how actors navigate the rich tapestry of established practices and innovative approaches. Through a comprehensive literature analysis, the study aims to uncover the key challenges and opportunities faced by actors in balancing tradition and progress. The methods section outlines the diverse methodologies employed in understanding the actors' experiences, followed by a presentation of results. The discussion section critically examines the findings, drawing connections between tradition, progress, and the evolving landscape of theatrical performance. Finally, the article concludes with insights and suggestions for actors and the broader theatre community.